2017
DOI: 10.2147/oaem.s129250
|View full text |Cite
|
Sign up to set email alerts
|

In-flight medical emergencies during airline operations: a survey of physicians on the incidence, nature, and available medical equipment

Abstract: BackgroundData on the incidence of in-flight medical emergencies on-board civil aircraft are uncommon and rarely published. Such data could provide information regarding required medical equipment on-board aircraft and requisite training for cabin crew. The aim of the present study was to gather data on the incidences, nature, and medical equipment for in-flight medical emergencies by way of a survey of physician members of a German aerospace medical society.Materials and methodsUsing unipark.de (QuestBack Gmb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 19 publications
0
22
0
2
Order By: Relevance
“…19 A recent German study in 2017 is in accordance with these results, reporting chest symptoms, circulatory collapse and altered mental status as the commonest cause of diversions. 20 Unsurprisingly, medical incidents causing diversions are associated with a higher death rate of 22%, compared with only 0.7% of all on-board medical emergencies. 16 This previously reported figure of 0.7% is similar to the 0.66% death rate (as a proportion of all emergencies) observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…19 A recent German study in 2017 is in accordance with these results, reporting chest symptoms, circulatory collapse and altered mental status as the commonest cause of diversions. 20 Unsurprisingly, medical incidents causing diversions are associated with a higher death rate of 22%, compared with only 0.7% of all on-board medical emergencies. 16 This previously reported figure of 0.7% is similar to the 0.66% death rate (as a proportion of all emergencies) observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from the current study indicate a higher number of incidents (n=3306 and 155/million passengers) versus 1312 (130/million passengers) medical incidents between 2011 and 2013 of a major flight company operating charter flights for less than 5 hours in Eurasia. 3 There were also more incidents per number of passengers; one event per 6432 passengers versus one event per 14 000 to 39 600 passengers as reported by other publications, 4 or one medical event per 50 flights versus one event per 63 flights reported in a German study. 7 The findings from the current study may possibly be attributable to the increased number of medical incidents on the international routes of the African airline (one medical event per 12 flights or 61 incidents per million passengers).…”
Section: Discussionmentioning
confidence: 79%
“…12 Cardiovascular disorders (40.0%) and neurological problems (17.8%) were the most frequent diagnoses described by aviation medicine physicians in Germany during an online survey. 4 The potential explanation for increased cardiopulmonary symptoms is that the reduced cabin pressure leads to a further reduction in oxygen saturation, which lowers even more with increasing flight times and can exacerbate medical conditions in passengers with pre-existing cardiac, pulmonary, and hematological conditions as they have a reduced baseline oxygen partial pressure (PaO2). 2 Oxygen was used in 46% of cases in this study, similar to the 48% in another study 12 but much higher than the 14% reported in Eurasian flights.…”
Section: Medical Conditions Encounteredmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature (described in Table 1) shows that medical incidents had been happening long before that but there are diverse themes related to their description and management (adequacy of medical resources (Hinkelbein et al, 2014;Hinkelbein, Neuhaus, Bö hm, Kalina, & Braunecker, 2017;Costa, 2015;Naouri et al, 2016), medico legal issues (Peterson et al, 2013;Costa, 2015;Bukowski & Richards, 2016), etc.). Researchers are watching at diverse ways of categorizing these medical incidents, as it concerns either number of flights or number of passengers.…”
Section: State Of the Artmentioning
confidence: 99%